2004
DOI: 10.1111/j.1478-3231.2004.0940.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of extracellular signal‐regulated protein kinase and its correlation with proliferation in human hepatocellular carcinoma

Abstract: Our findings suggest that ERK overexpression contributes to the proliferation of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 22 publications
(27 reference statements)
2
54
0
Order By: Relevance
“…Inhibition of ERK by dominant-negative ERK or antisense nucleotides of ERK exhibits the suppression of cell growth (Bottazzi et al, 1999). Previous studies have shown that overexpression of ERK in HCC is correlated with its proliferative activity (Ito et al, 1998;Tsuboi et al, 2004). The kinase activity of ERK is fully activated through the phosphorylation of threonine (Thr 202) and tyrosine (Tyr 204) of ERK by MAP kinase kinase (MEK), which is activated by Raf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of ERK by dominant-negative ERK or antisense nucleotides of ERK exhibits the suppression of cell growth (Bottazzi et al, 1999). Previous studies have shown that overexpression of ERK in HCC is correlated with its proliferative activity (Ito et al, 1998;Tsuboi et al, 2004). The kinase activity of ERK is fully activated through the phosphorylation of threonine (Thr 202) and tyrosine (Tyr 204) of ERK by MAP kinase kinase (MEK), which is activated by Raf.…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatocellular carcinoma (HCC), proliferative activity is higher even in precancerous lesions, such as adenomatous hyperplasia, than in the adjacent nontumorous liver tissue. Previous studies have shown that various growth factors enhance HCC cell proliferation through the activation of the Ras/Raf-1/ERK pathway and aberrant activation of this pathway is frequently observed in human HCC (Schmidt et al, 1997;Ito et al, 1998;Tsuboi et al, 2004), although most HCC tumors lack oncogenic Ras mutation. In addition, high tumor proliferation induced by ERK activation is closely linked to resistance against any type of therapy, including irradiation therapy and chemotherapy, resulting in shorter survival times for patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of human HCCs, the Erk/MAPK pathway has been described to be activated (Nijhara et al, 2001;Tsuboi et al, 2004). Once activated, TGF-b is supposed to switch to a tumorprogressive function in (pre)-cancerous hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, various growth factors were found to enhance HCC cell proliferation, as well as tu-mor invasion and metastasis, via the activation of the Ras/Raf-1/extracellular signal-regulated kinase (ERK) pathway (Nonomura, Ohta et al, 1987;Pang, Yuen et al, 2004;Tsuboi, Ichida et al, 2004). Also, overexpression of Ras genes is common in human HCC tissue.…”
Section: Introductionmentioning
confidence: 99%